Using simulation to estimate the cost effectiveness of improving ambulance and thrombolysis response times after myocardial infarction. Issue 1 (22nd December 2005) - Chase, D; Roderick, P; Cooper, K; Davies, R; Quinn, T; Raftery, J
Abstract : Objectives: To quantify the health gains and costs associated with improving ambulance and thrombolysis response times for acute myocardial infarction. Design: A computer simulation model. Patients/setting: Patients experiencing acute myocardial infarction in England. Interventions: Improving the ambulance response time to 75% of calls reached within 8 minutes and the hospital arrival to thrombolysis time interval (door-to-needle time) to 75% receiving it within 30 minutes and 20 minutes, compared to best estimates of response times in the mid-1990s. Main outcome measures: Deaths prevented, life years saved, and discounted cost per life year saved. Results: Improving the ambulance response to 75% of calls within 8 minutes resulted in an estimate of 5 deaths prevented or 57 life years saved per million population per year, with a discounted incremental cost per life year saved of £8540 over 20 years. The corresponding benefit of improving the door-to-needle time to 75% of myocardial infarction patients within 30 minutes was an estimated 2 deaths prevented and 15 life years saved per million population per year, with a discounted incremental cost per life year saved of between £10 150 to £54 230 over 20 years. Little further gain was associated with reaching the 20 minute target. Combining ambulance and thrombolysis targets resulted in 70 life years saved per million population per year. Conclusions: Improving ambulance response times appears to be cost effective. Reducing door-to-needle time will have a smaller effect at an uncertain cost. Further benefits may be gained from reducing the time from onset of symptoms to starting thrombolysis.